2021
DOI: 10.1590/2675-2824069.21019mc
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Sea we want

Abstract: Cappelletto et al.This paper presents major gaps and challenges for implementing the UN Decade of Ocean Science for Sustainable Development (2021)(2022)(2023)(2024)(2025)(2026)(2027)(2028)(2029)(2030) in the Mediterranean region. The authors make recommendations on the scientific knowledge needs and codesign actions identified during two consultations, part of the Decade preparatory-phase, framing them in the Mediterranean Sea's unique environmental and socio-economic perspectives. According to the 'Mediterran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
0
9
0
1
Order By: Relevance
“…Mesozooplankton abundance also follows this west-east gradient (Nowaczyk et al, 2011) with higher values found in the upper 100 m layer (Siokou et al, 2019). Coastal areas in the Mediterranean have variable hydrographic characteristics (Schroeder et al, 2013;Menna et al, 2021) and are seasonally exposed to different intensities of anthropogenic and terrestrial influences, which may affect the coastal marine ecosystems (Cappelletto et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…Mesozooplankton abundance also follows this west-east gradient (Nowaczyk et al, 2011) with higher values found in the upper 100 m layer (Siokou et al, 2019). Coastal areas in the Mediterranean have variable hydrographic characteristics (Schroeder et al, 2013;Menna et al, 2021) and are seasonally exposed to different intensities of anthropogenic and terrestrial influences, which may affect the coastal marine ecosystems (Cappelletto et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…In the last 30 years, CMEMS (Copernicus Marine Environment Monitoring Service) and other observational forecasting integrated systems have been established in the Mediterranean Sea to provide updates on the state of the basin. These products, however, are still limited to physics and to few main biogeochemical variables, and their resolution is not suitable to properly address the ecological features characterizing coastal areas (Cappelletto et al, 2021).…”
Section: Studies Connecting Organismsecosystems and Ecosystem Servicesmentioning
confidence: 99%
“…Models should be able to address the cumulative effect of OA and other stressors, also considering synergistic effects and non-linear interactions. This is crucial to better understand the multiple effects of changes in stressors and to explore adaptation/mitigation measures that can be applied at different spatial and temporal scales (Duarte et al, 2013;Zunino et al, 2021;Cappelletto et al, 2021). Furthermore, it would be important to at least try to incorporate organism plasticity and long-term adaptation in modeling ecosystem response, possibly also considering different life time-span of different organisms and therefore turnover rates (Solidoro et al, 2010).…”
Section: To Improve Oa Modeling Studies In the Mediterraneanmentioning
confidence: 99%
“…Implementing ocean risk reduction for increased safety can only be based on scientific achievements (Cappelletto et al, 2021). A multidisciplinary approach to observe, monitor and model, will promote more effective and sustainable management and development policies.…”
Section: Outcome 5: a Safe Oceanmentioning
confidence: 99%
“…In this direction many initiatives have already started. In the Mediterranean area, the SciNMeet Programme ("Science We Need for the Mediterranean Sea We Want") (Cappelletto et al, 2021) is aimed to address major challenges and gaps in scientific knowledge to manage regional impacts in consideration of emerging environmental issues. The Biomolecular Ocean Observing Network is developing a global system that will allow science and society to understand and protect ocean life and will also help communities to detect biological hazards.…”
Section: Outcome 5: a Safe Oceanmentioning
confidence: 99%